Controle inteligente para maximização da geração de potência em termogeradores - Bezerra, Carlos Daniel de Sousa (2019)
This work presents a theoretical and experimental analysis of the physical connection and intelligent control of DC-DC converters to the Seebeck thermoelectric generating system. The methodology is based on the application of heuristic optimization methods for the tuning of controllers, observing the transient and permanent responses. It is also developed methodology using artificial neural network associated with the control in voltage mode, necessary for the tracing of the maximum power of the thermogenerator. The computational mathematical model of voltage converter, thermogenerator, controller based on the place of roots, non-pre-phase systems and control techniques is described. The computational simulations and and the practical tests are validated. The results indicate the efficiency of the optimization methods in the tuning of the voltage controller and the best response times for neural networks as a mechanism for tracking the maximum power.